The interaction between selenium and other elements in soil and rice roots shaped by straw and straw biochar regulated the enrichment of selenium in rice grain - Rong, Qinlei; Chen, Jie; Zhang, Yufang; Tan, Zebin; Wang, Wanjing; Sun, Chunxia; Guo, Xi; Zhou, Chunhuo; Cai, Haisheng; Zhao, Xiaomin (Frontiers in Plant Science, 2024)
The absorption and transport of selenium (Se) in rice depend on the shared transport proteins and channels with other elements. However, the interactions between Se and other elements within the soil-rice system and their relationship with Se-enriched rice are still not well understood. Hence, we conducted pot experiments to investigate the transformation of Se forms in soil and the absorption and enrichment of Se in rice, which varied with nutrient other elements influenced by straw and straw biochar retuning in Se-rich red paddy soil. Partial Least Squares Path Modeling (PLS-PM) analysis was carried out to reveal the interaction between Se and other elements and crucial processes in Se enrichment in rice grains. The results showed that the incorporation of straw and straw biochar into the fields increased the content of soil soluble Se (SOL-Se) but significantly decreased the content of iron-manganese oxide-bound Se (FMO-Se) and organic matter-bound Se (OM-Se). Moreover, the rise in the soil bioavailable Se was mainly attributed to the activation of FMO-Se and OM-Se. Compared with the NPK treatment, the contents of Se in rice grain were increased by 69.22% and 38.09%, under straw and biochar returning, respectively. However, the contents of Se in leaves decreased. The variance partitioning analysis (VPA) indicated that the migration of Se in rice plant was significantly influenced by differences in rice tissues and their nutrients interactions (nitrogen (N), phosphorus (P), potassium (K), and Se), explaining 51.5% and 35.3% of the variations in Se content in different rice parts, respectively. The PLS-PM analysis demonstrated that the absorption of Se by rice roots and its transportation from leaves to grains were crucial processes affecting Se enrichment in rice. However, these processes were modulated by soil properties and root nutrients interaction (N, P, and Se) induced by straw and straw biochar incorporation. The present study provides further understanding of the main factors and key processes in regulating Se absorption and transformation in the soil-rice system, and to more efficiently utilize Se-rich paddy fields through agricultural management measures.